Nodule count effect on microstructure and mechanical properties of hypo-eutectic ADI alloyed with nickel - Colin-García, Eduardo; Cruz-Ramírez, Alejandro; Romero-Serrano, José Antonio; Sánchez-Alvarado, Ricardo Gerardo; Gutiérrez-Pérez, Víctor Hugo; Reyes-Castellanos, Guillermo (Journal of Mining and Metallurgy, Section B: Metallurgy, 2021)
Samples of ductile iron alloyed with 0.88 % Ni with a nodule count of 606, 523, and 290 nod mm-2 were obtained from sand cast plates of different thickness in the range from 25.4 to 8.46 mm. The effect of the nodule count was evaluated during the austempering process held at 285 °C and austempering times of 15, 30, 45, 60, 70, and 90 min. The volume fraction of high carbon austenite was increased when the nodule count was increased. The process window was narrow, requiring a lower austempering time when the nodule count was increased. The combination of a higher nodule count and low austempering temperature allows obtaining a fine ausferritic microstructure which leads to obtaining higher Brinell hardness and tensile strength. The process window was determined by XRD measurements and it is in good agreement with the microstructural and hardness evolution as the austempering time was increased.